HUBUNGAN KEMAMPUAN SUPERVISI KEPALA RUANGAN DENGAN PELAKSANAAN DOKUMENTASI ASUHAN KEPERAWATAN - David Ginting; Yesika Widiawati Harahap (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2019)
Nursing care documentation is a nursing record that provides information about the client's condition, which can be used as evidence of a nurse's responsibility and accountability in carrying out his duties. Documentation by nurses is very important, so supervision is needed to ensure that the records are in accordance with the standards. This study aims to determine the relationship between the supervising capacity of the head of the room and the implementation of nursing care documentation, with the type of quantitative research being analytic with a cross sectional approach. The population in this study were all nurses who served in the inpatient ward of Grandmed Hospital. Data analysis was carried out by chi square test at 95% confidence level (Î± = 0.05). The results showed that there was a relationship between the supervision capacity of the head of the room and the implementation of nursing care documentation p value (= 0.009) <Î± (= 0.05). For the Nursing Field of Grandmed Hospital to carry out supervision in accordance with the standards and carried out regularly 2 times a week.